$\tilde{g}$(1,2)*-closed Sets in Bitopological Spaces - K. M. Dharmalingam; A. Thamilisai; O. Ravi (International Journal of Mathematics And its Applications, 2015)
In this paper, we offer a new class of sets called $\tilde{g}$(1,2)*-closed sets in bitopological spaces and we study some of its basic properties. It turns out that this class lies between the class of $τ$$_{1,2}$-closed sets and the class of (1,2)*-$α g$-closed sets.